Investigating the Harmful effects of Fossil Fuel Consumption Subsides on Power Generation Costs in Iran - Sadaf Ziyaei; Mostafa Panahi; Davoud Manzour; Abdolreza Karbasi; Hamidreza Ghaffarzadeh (Environmental Energy and Economic Research, 2021)
The current system of fuel consumption subsides payments of fossil power plants in Iran has initiated substantial challenges such as controversies on real price and total costs of the electricity in Iran. The main objective of this study is the calculation and assessment of the total costs of electricity generation in different existing power plants in Iran including thermal and renewable power plants on the basis of figures of real and Subsidy fuel costs using a variety of discount rate. For this purpose, the technique of electricity Levelized costs has been used. The obtained results of this study indicate when the LCOE is calculated with the Subsidy cost of fuel, the least amount of electricity generation costs applies to fossil power plants. Meanwhile, this can be considered true if the real fuel value is taken into account in Iran, the least amount of power generation cost will be imposed on the renewable power plants. We also showed how the investment risk in this sector will change by changing the discount rate in the calculation method. Results showed that the energy system is strongly affected by changes in discount rates. The lower discount rate is the higher the renewable contribution. Obviously, if the policy of subside payment to the state energy sector continues, the total costs of electricity generation in Iran will still be unrealistic due to unreal costs of delivery fuel to the power plants and the employment of renewable energies will not be capable of competing with fossil fuels.